2013
DOI: 10.1007/s10900-013-9719-4
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis: A Study of Knowledge, Attitude and Practice Among Adults in Riyadh, Saudi Arabia

Abstract: Osteoporosis is a growing chronic health problem that could result in mortalities and poor living quality. This study aimed at assessing the awareness of adults in Riyadh about this disease and its associated factors as well as compare KAP levels of men and women. A cross sectional study including 505 participants was conducted in several malls of Riyadh city during March 2012, selected by stratified random sampling technique. Self-administered questionnaire was used for data collection. 86% of the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
62
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 10 publications
10
62
5
Order By: Relevance
“…However, another study among adults in Riyadh showed that participants' knowledge score was about 57 % of the total score and practice score was 51.7 % (22) . These scores are higher than our results and this could be attributed to different age and population size between the two studies.…”
Section: Discussion:-mentioning
confidence: 93%
“…However, another study among adults in Riyadh showed that participants' knowledge score was about 57 % of the total score and practice score was 51.7 % (22) . These scores are higher than our results and this could be attributed to different age and population size between the two studies.…”
Section: Discussion:-mentioning
confidence: 93%
“…In consistence, Al-Otaibi showed that Saudi women had a deficient knowledge and practice scores about osteoporosis (14) . Also, other studies that was conducted in Assir region and Riyadh showed a poor KAP of osteoporosis (9,12,15,16) .…”
Section: Discussion and Conclusion:-mentioning
confidence: 96%
“…The good awareness and practice pattern toward osteoporosis is recommended for good prevention of the disease (12) . Little is known about osteoporosis among Saudi population hence further investigations are needed to assess the KAP of Saudi patients for prevention of osteoporosis and its complications (8,9,12) .…”
Section: Discussion and Conclusion:-mentioning
confidence: 99%
See 2 more Smart Citations